Innovation limb splinting for intravenous cannulae in pediatric - Sofiyawati, Estri; Ayunitias, Imelda; Santosa, Agus (Universitas Muhammadiyah Purwokerto, 2021)
Background: Currently, the splint used in the hospital is not yet practical; it still requires a long installation time and causes the child to experience anxiety when the infusion is installed. Thus, a limb splinting innovation is needed to ease nurses' inserting the needle infusion and reduce young patients' anxiety.Technic: This splint uses a wood material covered with foam, wrapped in a cotton fabric having cartoon printing, and it has an adhesive cloth at its bottom. It has a hole at the top to monitor the needle that goes into the vein.Conclusion: This innovative splint is proven to be easier to use to fix the infusions in children. It is safer and more comfortable. It indeed can reduce anxiety symptoms in children during the infusion.